SPE International Oilfield Scale Conference and Exhibition 2014
DOI: 10.2118/169798-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sulphide Scale (PbS/ZnS) Formation and Inhibition Tests for a Gas Condensate Field with Severe Scaling Conditions

Abstract: Identifying effective sulphide scale squeeze inhibitors has been a major challenge in the production of oil and gas from deeper, higher temperature reservoirs. Managing sulphide scales of zinc and lead (ZnS and PbS) that commonly occurs in deep, hot reservoirs poses a significant challenge because of their very low solubilities. In general, for scaling problems applying chemical scale inhibitors or dispersants is the preferred solution to most challenges. However, to date no effective sulphide inhibitors/dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The procedure more closely reflects mechanisms and conditions during production within a sour production well, where pressure-volume-temper- ature (PVT) studies have shown that aqueous H 2 S concentrations reach up to approximately 55 ppm at equilibrium, and turbulent, two-phase flow conditions are generated in an anaerobic environment. 7 Further experiments, contrasting the precipitation and deposition mechanisms of "conventional" carbonate and sulfate scales onto antifouling surfaces, supplant current notions within the oil and gas industry that metal sulfides nucleate directly onto surfaces, 6,8 instead highlighting the role of the light oil phase on homogeneous scale adhesion. The design and development of an airtight delivery vessel allowed introduction of incompatible seawater and formation water brines under anaerobic conditions.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The procedure more closely reflects mechanisms and conditions during production within a sour production well, where pressure-volume-temper- ature (PVT) studies have shown that aqueous H 2 S concentrations reach up to approximately 55 ppm at equilibrium, and turbulent, two-phase flow conditions are generated in an anaerobic environment. 7 Further experiments, contrasting the precipitation and deposition mechanisms of "conventional" carbonate and sulfate scales onto antifouling surfaces, supplant current notions within the oil and gas industry that metal sulfides nucleate directly onto surfaces, 6,8 instead highlighting the role of the light oil phase on homogeneous scale adhesion. The design and development of an airtight delivery vessel allowed introduction of incompatible seawater and formation water brines under anaerobic conditions.…”
Section: Introductionmentioning
confidence: 88%
“…In this study, a new method and apparatus whereby H 2 S gas is introduced into the air-space of an anaerobic reaction vessel, gradually diffusing into the aqueous phase before reaching equilibrium and dissociating into reactive bisulfide (HS − ) species, is employed. The procedure more closely reflects mechanisms and conditions during production within a sour production well, where pressure-volume-temperature (PVT) studies have shown that aqueous H 2 S concentrations reach up to approximately 55 ppm at equilibrium, and turbulent, two-phase flow conditions are generated in an anaerobic environment . Further experiments, contrasting the precipitation and deposition mechanisms of “conventional” carbonate and sulfate scales onto antifouling surfaces, supplant current notions within the oil and gas industry that metal sulfides nucleate directly onto surfaces, , instead highlighting the role of the light oil phase on homogeneous scale adhesion.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation